Leisure necessities and symbolic meaning of traveling through habitus on social media - Rewindinar, Rewindinar (Bricolage : Jurnal Magister Ilmu Komunikasi, 2026)
Social media allows people to share what they do in the real world through their posts on social media. However, what they present online are not based on reality. Posts on social media increasingly illustrate differences in social status because even though the posts are on the same topic and category, they show different tastes. Through Bourdieu’s thought that tastes are determined by social structure, this study aimed to explore how a person’s consumption, especially traveling, can change due to habitus in social media. Consumption in Bourdieu's explanation is no longer determined by economic factors, but by culture. Cultural practices in technology play a role in changing consumption patterns in society. As a communication process that builds simulations and social space, social media posts create distinctions in society. The narrative method used to understand individuals’ experiences are subjective and interpreted in their world, so they have an objective impact. Interviews were carried out with Indonesian travelers who provided recommendations for their followers who have the same interests in traveling. In addition, the netnography method was carried out to see the meaning of traveling in modern society. This study shows that traveling has become a symbol. This change in traveling consumption provides confirmation for social media as a process of transformation through habitus.